Possibilities of enhancing the colour of egg yolk - Dvořák, Petr; Suchý, Pavel; Straková, Eva; Kopřiva, Vladimír (Journal of the science of food and agriculture, 2012)
BACKGROUND: This study attempts to compare two possibilities of enhancing the colour of egg yolk. One of them is based on the ecological rearing of laying hens on natural green grass whereas the other uses a feeding dose supplemented with natural pigments in laying hens reared in individual cages. Is it possible to distinguish these two technologies using yolk colour determination in the CIELAB system? RESULTS: Yolk colour parameters such as L*, a*, and b* in the group of grazed hens are significantly different (α = 0.001) from those observed in hens reared in cages. The yolk colour shows a darker, redder and more yellow colour. The greatest difference was seen in the red colour parameter, a*, that increased more than twice. Visually, this means a shift towards a more orange colour. Compared to grazing in the meadow (ΔE* = 13.257), the addition of artificial pigments in the feed resulted in a more significant increase in the parameter ΔE* (CIE total colour difference), with the greatest value of ΔE* being observed with the use of both pigments (ΔE* = 24.265). CONCLUSION: Grazing increases the parameter a* whereas the values of the parameter C*(ab) remain relatively low. The parameter ΔE* is significantly lower in the case of grazing as compared to the supplementation of the feed with pigments. However, colourity parameters cannot be used as a specific standard to identify a particular grazing technology as their values vary during the laying period.
Keywords: Animals, Inbred Strains; Female; Animals; vaječný žloutek; Animal Husbandry; xanthofyly; biologické pigmenty; Tagetes; Animal Feed; Chickens; Flowers; Czech Republic; chov zvířat; zvířata; květy; Egg Yolk; ženské pohlaví; Xanthophylls; kur domácí; Pigments, Biological; Česká republika; inbrední kmeny zvířat; Poaceae; lipnicovité; krmivo pro zvířata